2019
DOI: 10.1002/mrd.23092
|View full text |Cite
|
Sign up to set email alerts
|

Research on the establishment of chronic stress‐induced premature ovarian failure the rat model and effects of Chinese medicine Muniziqi treatment

Abstract: The purposes of this study were to establish and to explore the biological basis of the chronic stress‐induced premature ovarian failure (POF) model and to explore the therapeutic effects of the traditional Chinese medicine Muniziqi. Sexually matured female Sprague–Dawley rats were fed with spinach and cilantro in cold and wet conditions for about 20 weeks until a chronic stress (CS) model was established. The CS rats were divided into a POF stress model group and a stress model group according to weekly biolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Xie et al reported that the Huyang Yangkun formula repaired dysfunctions in POI rats through the Hippo-JAK2/STAT3 pathway [ 24 ]. Keremu et al reported that TCM Muniziqi improved the function of the hypothalamus-pituitary-ovarian axis in POF rats [ 25 ]. TCM could treat POF that is caused by apoptosis or immunosuppression [ 26 , 27 ].…”
Section: Application Of Traditional Chinese Medicine In Pofmentioning
confidence: 99%
“…Xie et al reported that the Huyang Yangkun formula repaired dysfunctions in POI rats through the Hippo-JAK2/STAT3 pathway [ 24 ]. Keremu et al reported that TCM Muniziqi improved the function of the hypothalamus-pituitary-ovarian axis in POF rats [ 25 ]. TCM could treat POF that is caused by apoptosis or immunosuppression [ 26 , 27 ].…”
Section: Application Of Traditional Chinese Medicine In Pofmentioning
confidence: 99%
“…In traditional Chinese medicine (TCM), most doctors agree that the main pathogenesis of POI is kidney deficiency and blood stasis, so BHD is also extensively applied in treating POI [24]. More and more studies have shown that chronic stress is an important cause of decreased ovarian function and reproductive endocrine disorders [25][26][27], and BHD can restore serum levels of follicle-stimulating hormone (FSH) and anti-Müllerian hormone (AMH) in POI rats induced by the stress hormone corticosterone and can reduce follicular atresia and improve ovarian function. A mechanistic study also showed that BHD might regulate the expression of Np4 and Angptl 4 to improve corticosterone-induced POI [28].…”
Section: Bhdmentioning
confidence: 99%
“…Stress can activate the hypothalamic-pituitary-adrenal axis, leading to prolonged abnormal endocrine hormone levels in women, ultimately resulting in menstrual disorders, infertility, and other reproductive dysfunctions [9]. In animal experiments, chronic stress has been shown to disrupt the estrous cycle, alter hormone levels, and decrease follicle numbers in mice [10,11]. Stress can also induce cytoplasmic fragmentation, apoptosis, spindle disorders, and oxidative stress, accelerating the aging of mouse oocytes and increasing the risk of early pregnancy failure [12].…”
Section: Introductionmentioning
confidence: 99%